Toward the recognition of user activity based on user location in ubiquitous computing environments - Mantoro, Teddy; Ayu, Media Anugerah (CSC Journals, 2008)
Human Activity is not a well defined concept in Ubiquitous Computing discipline because human activity is very complex and the computer environment is very limited in capturing user activity. However, user activity is an essential ingredient for the determination of appropriate response from Intelligent Environment in order to provide appropriate services with or without explicit commands. This paper describes an approach to the determination and recognition of user activity based on user location. The characterisation of user activities can be deduced from sensor activities based on the scalable distribution of context location information. This approach does not require users to label their activities.